A Invisibilidade da arte indígena contemporânea no Currículo Paulista de Arte - Mathias, Elisângela de Freitas (Farol, 2022)
The Student’s Notebook is a document that aims to assist in the development of the skills proposed by the São Paulo Art Curriculum and consists of Learning Situations, with proposals for activities to be put into practice in the classroom. The objective of this article is to propose an analysis of the activities suggested in Caderno do Aluno, from the 8th year of Elementary School, to understand how indigenous visual arts are approached. Such analysis will be based on comparing the skills proposed by the Currículo Paulista de Arte with the video material available in these notebooks. The hypothesis intended here is to show that the indigenous visual arts are silenced, made invisible and treated as a subterfuge to comply with a mandatory law, otherwise, for example, we would have the contemporary artistic productions of the indigenous people themselves as material for study.